Education for Tomorrow A Biocentric, Student-Focused Model for Reconstructing Education - Risku, Michael; Harding, Letitia; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Education for Tomorrow A Biocentric, Student-Focused Approach to Education Reform Michael Risku University of the Incarnate Word, USA and Letitia Harding University of the Incarnate Word, USA There are many books on the market which discuss indigenous ways of knowing, and bemoan western society$1 (Bs seeming lack of interest in anything other than scientific fact-based knowledge. Equally plentiful are the writings of critical theorists who consider today$1 (Bs public education system to be divisive, and manipulated by those in power to ensure that their children have the educational advantages needed to maintain the elite hierarchical status quo. Education for Tomorrow is unique in that it brings both of these approaches together first by examining the ways that indigenous people and women of all cultures acquire and pass on knowledge, and the deleterious effects that enforced Eurocentric systems have had on that process. The authors then turn to public schools to explore the influences, both good and bad, that today$1 (Bs programs have on the distribution of opportunities afforded to all children in the United States. Finally, they offer suggestions for a revolutionary education system which highlights the need for all students to have the encouragement and freedom to look critically and rationally at their lives and at their relationship with the natural world. This can be achieved by looking back to the pedagogical methods of our indigenous ancestors, and forward to a time when all children, regardless of ethnic or socio-economic heritage, are taught in such a way that every aspect of their lives is addressed, nurtured, valued, and enhanced.s
Keywords: Education; Education; Education (general).